Eco-anxiety: What it is and why it matters - Kurth, Charlie; Pihkala, Panu (Frontiers in Psychology, 2022)
Researchers are increasingly trying to understand both the emotions that we experience in response to ecological crises like climate change and the ways in which these emotions might be valuable for our (psychical, psychological, moral) wellbeing. However, much of the existing work on these issues has been hampered by conceptual and methodological difficulties. As a first step toward addressing these challenges, this review focuses on eco-anxiety. Analyzing a broad range of studies through the use of methods from philosophy, emotion theory, and interdisciplinary environmental studies, the authors show how looking to work on anxiety in general can help researchers build better models of eco-anxiety in particular. The results of this work suggest that the label “eco-anxiety” may be best understood as referring to a family of distinct, but related, ecological emotions. The authors also find that a specific form of eco-anxiety, “practical eco-anxiety,” can be a deeply valuable emotional response to threats like climate change: when experienced at the right time and to the right extent, practical eco-anxiety not only reflects well on one’s moral character but can also help advance individual and planetary wellbeing.